Tumor Microenvironment‐Driven Structural Transformation of Vanadium‐Based MXenzymes to Amplify Oxidative Stress for Multimodal Tumor Therapy - Zhu, Hai; Li, Tinghua; Peng, Xinhao; Zhang, Xiaoxian; Zhang, Xuequan; Wang, Qiusheng; Lei, Lei; Zhang, Jun; He, Bin; Cao, Jun (Advanced science, 2025)
MXenzymes, a promising class of catalytic therapeutic material, offer great potential for tumor treatment, but they encounter significant obstacles due to suboptimal catalytic efficiency and kinetics in the tumor microenvironment (TME). Herein, this study draws inspiration from the electronic structure of transition metal vanadium, proposing the leverage of TME specific‐features to induce structural transformations in sheet‐like vanadium carbide MXenzymes (TVMz). These transformations trigger cascading catalytic reactions that amplify oxidative stress, thereby significantly enhancing multimodal tumor therapy. Specifically, the engineered HTVMz, coated with hyaluronic acid, exhibits good stability and generates a thermal effect under NIR‐II laser irradiation. The thermal effect, combined with TME characteristics, facilities a structural transformation into ultra‐small vanadium oxide nanozymes (VOx). The enlarged surface area of VOx substantially enhances ROS regeneration and amplifies oxidative stress, which promotes lysosomal permeability and induces endoplasmic reticulum stress. The high‐valent vanadium in VOx interacts with intracellular glutathione, disrupting redox homeostasis and intensifying oxidative stress further. These amplifications accelerate tumor apoptosis, induce ferroptosis, and suppress HSP90 expression. Consequently, the heightened thermal sensitivity of HTVMz synergistically promotes tumor cell death via multimodal therapeutic pathways. This study presents an innovative strategy for tumor catalytic therapy by manipulating MXenzymes structures, advancing the field of catalytic therapy. This study introduces a novel strategy that uses the TME to trigger structural changes in vanadium carbide MXenzymes, converting them into ultra‐small vanadium oxide nanozymes. These transformations enhance oxidative stress, promoting tumor apoptosis, ferroptosis, and lysosomal permeability. The synergy of thermal response and catalytic reactions boosts antitumor efficacy through thermal, oxidative, and catalytic mechanisms.